A Meta-Analysis Study in Explaining the Role of Segmentation, Targeting, and Positioning Strategy on Culinary SMEs in Luwuk Banggai - Tafsir, Muh.; Lamato, Riski Mahyudin (Entrepreneurship, Management, and Business Research Journal, 2025)
This meta-analysis study investigates the roles of segmentation, targeting, and positioning (STP) strategies in enhancing the performance of culinary small and medium enterprises (SMEs) in Luwuk Banggai, Indonesia. By synthesizing existing literature, the study aims to elucidate how effective STP strategies contribute to competitive advantage and market success for culinary SMEs in this region. The findings reveal that well-defined segmentation, precise targeting, and strategic positioning are critical for meeting customer needs and preferences, ultimately driving growth and sustainability in the culinary sector.